The effectiveness of rock phosphate fertilizer toward the growth and production of oil palm / Ahmad Zahin Azfar Buniyami - Buniyami, Ahmad Zahin Azfar (Faculty of Plantation and Agrotechnology, 2017)
Oil palm (Elaeis guineensis) was originally from West Africa where it grows wild and later was developed into an agricultural crop. Amongst the commercial vegetable oil crops in the world, the oil palm agro-ecosystem produces the largest quantity of edible oil per unit area despite being largely grown on highly weathered tropical soils with low soil fertility such as Malaysia. Fertilizing is the one of the important factors that oil palm plantation keep success in this sector because oil palm needed good nutrient management. Phosphorus is an essential element for plant growth and important for the establishment of root growth at early stages. Rock Phosphate is the one of the Phosphorus source that had been used in agricultural sector. It is therefore that Rock Phosphate fertilizers have been pivotal to well-being of oil palm and the profitability and sustainability of oil palm industry. This paper review discusses about the effectiveness of Rock Phosphate fertilizer toward the growth and production of oil palm in immature and mature stage which is compared four type of P fertilizer consists of Christmas Island Rock Phosphate(CIRP), Morocco Rock Phosphate(MRP), Sokoto Rock Phosphate(SRP) and Single Super Phosphate(SSP). Therefore, it is effective using P fertilizer on oil palm which is needed to apply the correct amount of type of P fertilizer. The result showing that there are significant differences between application of P fertilizer and without P application on growth and production of oil palm. Besides that, the reactivity of Rock Phosphate fertilizers also affect the growth performance as discussed in this review.